Barriers in cancer risk reduction in community in Indonesia: a qualitative study - Tiranda, Yulius; Nuntaboot, Khanitta; Septiwi, Cahyu; Agianto, Agianto; Solikhah, Solikhah (International Journal of Public Health Science (IJPHS), 2024)
Integrated development post of non-communicable diseases (Posbindu penyakit tidak menular/PTM) is one of the strategies implemented by the MOH of Indonesia for prevention, screening, and early detection through community empowerment and community involvement in reducing the number of non-communicable diseases (NCDs), including cancer. This study aimed to explore the barriers to reducing the risk of cancer. Twelve participants were involved in this study using in-depth interviews and participant observations. All the interviews and discussions were recorded using an audio tape recorder and also using field notes, and then a transcript was transcribed verbatim. Five themes emerged namely providing funding for the program, obtaining appropriate support from the government based on the community’s needs and a health workforce shortage, sharing and discussing the health information, and cultural practices of the community as barriers to reducing the risk of cancer in the community. The study results can be used as evidence to develop and sustain effective strategies to address the barriers to reducing the risk of cancer in communities in Indonesia.